DINAMIKA ELITE KESULTANAN TERNATE DALAM PERUBAHAN REZIM: KESULTANAN TERNATE PASCA KEMERDEKAAN RI - Hasim, Rustam (Universitas Hasanuddin, 2024)
This paper explains the political situation in the Ternate region during the Soekarno era. The foundation that gave a noble position to the nobility (which had been changed during the Dutch colonial era), was again hit by the construction of the ideology of state nationalism, which prioritized the basis of loyalty to the state. The role and position of the autonomous elite in the Ternate Sultanate which had been enjoyed for centuries, was challenged by the construction of the ideology of a unitary state that prioritized the basis of loyalty to the state by separating public positions in a modern political format with traditional power. Thus a sultan does not automatically become a governor or regent but is elected through a contestation through a political party or positions in the bureaucracy are no longer something that is genealogically attached but must be based on certain competencies.